Cosmogony and worldview in the rationality and cocama-cocamilla thought - Hagiwara Grández, Ferdinand (2014)
The new intercultural trends seek to recover knowledge of ancestral peoples long forgotten or minimized until nihilization by ethnocentric drift of European origin. To determine whether conquered or colonized peoples of America have had own rational ways (to wit philosophies) has always been a topic of discussion. The encounter between Europeans and Americans entailed a culture shock between two ways of understanding the world, two different rationalities, which put one over the other by the mere fact of implying a power relationship: winners and losers; the latter were placed on the edge of barbarism and the former at the pinnacle of culture and civility, which in the long run has led to unambiguous interpretations of what is the ideal of man (the european is the prototype par excellence), with the subsequent minimization of the native American man. This has led to a cultural reductionism, since it denies others “types of man”, not even an attempt was made to discover them. In any case, this article attempts a new approach of this problem in the amazonian world, a new look in the light of divergent thinking and a new paradigm of complexity in a representative ethnicity of this world: The Cocama-Cocamilla, once rulers of the river and the forest.